Fostering The Discipline Of Students In Murajaah Al-Qur'an - Novri Efendi; Mega Adyna Movitaria; Halim Andana (Institut Agama Islam Sumatera Barat, 2023)
Memorizing the Al-Qur'an is obligatory and Allah has guaranteed the ease of memorizing it, but at the memorization level many find it very difficult, one way to overcome this is to use the muraja'ah method, namely repeating the reading that has been obtained so that you don't forget. The author focuses on the problem (a) how is the application of the murajaah method in strengthening the memorization of the Qur'an? (b) supporting and inhibiting factors. This study uses a qualitative descriptive field method, with observation, interviews, and documentation techniques. The data analysis technique used is data reduction, data presentation, and drawing conclusions. Data checking was carried out using triangulation, namely source and technique triangulation. The results showed that, (1) the murajaah method applied at the Syifa Orphanage has 5 techniques, namely murajaah to the teacher, murajaah by listening to individual methods, murajaah by listening to groups, murajaah alone and murajaah by listening to two people. The results of the memorization tests that have been carried out show that the memorization that has been memorized is stronger than the memorization that has not been memorized. . As for the inhibiting factors, the limitations of the teacher and the time of the condition of the students include background, fatigue, boredom and laziness